Evaluation of bi-directional causal association between periodontitis and benign prostatic hyperplasia: epidemiological studies and two-sample mendelian randomization analysis - Wei, Haotian; Tian, Guangjie; Xu, Shendan; Du, Yaqi; Li, Minting; Wang, Yonglan; Deng, Jiayin; Quan, Changyi (Frontiers in Genetics, 2024)
Background: Periodontitis and benign prostatic hyperplasia (BPH) are all common chronic diseases with higher incidence in middle-aged and old men. Several studies have indicated a potential association between periodontitis and BPH, although the findings remain inconclusive. However, there is no mendelian randomization (MR) studies to assess this association. Methods: The 40 men who had received health check-ups were included in an epidemiological study. Genetic data of BPH (13118 cases and 72799 controls) and periodontitis (3046 cases and 195395 controls) from FinnGen project was used to perform two-sample MR analysis. The Inverse Variance Weighted (IVW) model was identified as the primary analytical method, with MR Egger, weighted median, simple mode, and weighted mode serving as additional approaches. Results: The epidemiological analysis demonstrated a lack of statistically significant differences in the prevalence of clinical BPH between severe periodontitis group and non-severe periodontitis group. Similarly, no statistically significant differences were found in the prevalence of severe periodontitis among individuals with clinical BPH compared to those without. Additionally, Among the five models utilized in MR analysis, including the IVW model, no evidence of a causal link between periodontitis and BPH was observed. Conclusions: The findings from our epidemiological investigation and MR analysis do not provide support for a causal relationship between periodontitis and BPH.